Penerapan Proses Seleksi dan Penempatan Kerja terhadap Kinerja Karyawan - Retla Della Rustawan; Nor Norisanti; Kokom Komariah (IPM2KPE, 2019)
The purpose of this study was to determine the effect of the application of work selection and placement processes on employee performance. The method used in this study uses descriptive methods and associative methods. Data collection techniques conducted by researchers in the study are through observation, questionnaire interviews, documentation and literature study. The data analysis technique starts from compiling data, tabulating data until the testing phase. The results of the study, based on the calculation of the categorization of data found that the value of the selection process is 571 between the criteria of medium and high. This shows that the selection process that occurred at PT. West Java and Banten Tbk Development Bank. Sukabumi Branch is already high. This means that the selection process has an effect on the company. Based on the calculation of categorization of data obtained that the value of work placements of 359 is between the criteria of low and medium. This shows that work placements that occur at PT. West Java and Banten Tbk Development Bank. Sukabumi Branch is classified as medium. Conclusions, selection and job placement on employee performance have a positive and significant effect Keywords: Application of Selection Process, Job Placement and Employee Performance